2009 IEEE Globecom Workshops 2009
DOI: 10.1109/glocomw.2009.5360740
|View full text |Cite
|
Sign up to set email alerts
|

Time-Domain Approach to Energy Efficiency: High-Performance Network Element Design

Abstract: YearFabrication Technology Slot capacity (full-duplex) Energy Efficiency*

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Indeed, Chabarek et al [5] reported that router power consumption in the idle state is only 10% less than that for the fully loaded state. Almost the same data were reported in [6]. This is because Internet traffic rapidly fluctuates and so it is very difficult to predict future traffic volume, which is necessary to control routers.…”
Section: Introductionmentioning
confidence: 79%
“…Indeed, Chabarek et al [5] reported that router power consumption in the idle state is only 10% less than that for the fully loaded state. Almost the same data were reported in [6]. This is because Internet traffic rapidly fluctuates and so it is very difficult to predict future traffic volume, which is necessary to control routers.…”
Section: Introductionmentioning
confidence: 79%
“…The power consumption of switches and routers has been characterized in different studies such as [23,24] and our own study in [25]. The results show that once the switch is powered on and its ports are activated, the power consumption is close to its maximum value.…”
Section: Prior Studies On Switch Energy Consumptionmentioning
confidence: 92%
“…The results show that once the switch is powered on and its ports are activated, the power consumption is close to its maximum value. For example in [24] that value is around 90% of the peak power consumption for a core router. That means that only 10% of the peak power consumption is dependent on the traffic load.…”
Section: Prior Studies On Switch Energy Consumptionmentioning
confidence: 99%
“…p t ) is shown in column four, and the idle power (i.e. p 0 ), which is typically 90% of the maximum power [23], is denoted in column five. The energy per bit (i.e.…”
Section: Average Power Consumption P U Of the Netbook Computermentioning
confidence: 99%